Oasis evolution processes and mechanisms in the lower reaches of Heihe River, Inner Mongolia, China since 1 ka ago. (March 2015) - Zhao, Hui; Sheng, Yongwei; Zhang, Jiawu; Zhao, Yan; Li, Guoqiang
Two major oases in the lower reaches of Heihe River, Inner Mongolia of China, the desertified ancient Juyanze oasis (AJO) and the modern Ejina oasis (MEO), experienced dramatic environmental changes and human migrations as documented in historic records. The processes and mechanisms of their evolution are the key for us to understand the environmental changes and human activities in this region, yet are still unclear. This study provides an evolution chronology of these two oases by analyzing the optical dating records from MEO and 14 C dating records from AJO and discusses their evolution mechanisms based on drainage network analysis and field investigations. The optical dating samples collected from aeolian sands below humus layers in Populus euphratica woodlands on MEO indicate that this oasis developed between 1.05 and 0.45 ka ago, while the 14 C dating samples collected from a number of dead P. euphratica trees from AJO consistently suggest that the complete desertification of AJO occurred before 400 cal. a BP. These new dating results imply that the two oases evolved simultaneously but in opposite directions. That is, AJO desertified while MEO developed gradually in the last 1 ka. Climate change occurring over the last 1 ka in northern China cannot explain the opposite evolution directions of these two adjacent oases. The drainage network analysis based on digital elevation models (DEMs) and field observations and the dates ( 0.5 ka) of the top lacustrine layer from GaxuNur Lake north of MEO suggest that the evolution of the two oases was mainly governed by Heihe River migration.